Terrain Awareness Using a Tracked Skid-Steering Vehicle With Passive Independent Suspensions - Galati, Rocco; Reina, Giulio (Frontiers in Robotics and AI, 2019)
This paper presents a novel approach for terrain characterization based on a tracked skid-steer vehicle with a passive independent suspensions system. A set of physics-based parameters is used to characterize the terrain properties: drive motor electrical currents, the equivalent track, the power spectral density for the vertical accelerations and motor currents. Based on this feature set, the system predicts the type of terrain that the robot traverses. A wide set of experimental results acquired on various surfaces are provided to verify the study in the field, proving its effectiveness for application in autonomous robots.